Health care systems and “auge” reform in Chile - Zúñiga Fajuri, Alejandra (Acta Bioethica, 2007)
Through the classification of health care systems in terms of their financing, number of stakeholders and consequences for health care equity, this essay pretends to analyze some of the changes that have taken place in Chile due to the health care reform system "AUGE" (Universal Access to Explicit Guarantees). Pending tasks are examined for conversion to the system that, while maintaining its mixed character, may be able to overcome its present strongly regressive consequences.